ANALISIS KADAR PROTEIN PADA DAGING IKAN NILA SEGAR (Oreochromis Niloticus) ASAL KECAMATAN CIKAJANG KABUPATEN GARUT - Dani Sujana (Akademi Kesehatan John Paul II Pekanbaru, 2020)
Protein is a nitrogen containing substance that is an imfortant factor for body function. In most body tissues, protein is the larges component after water. Protein components are essential for the replacement of tissues, energy supplies, and versatile macromolecules in all biological processes as catalysts, transporting various other molecules such as oxygen, immune, and delivering nerve infusions. This research is conducted by qualitative and quantitative test. Qualitative test with biuret method while quantitative test with Kjeldahl method. White the aim to determine the protein levels in tilapia (Oreochromis niloticus) who was 1 month, 2 month, and 3 month districts Cikajang Garut. The results obtained by qualitative test with biuret method is characterized by the formation of violet to purple. In the quantitative test with Kjeldahl method, the results obtained in 1 month old tilapia are 1,419%, 2 months are 1,788%, 3 months is 2,15%.